In Place Leaching of a Mixed Copper Ore Body - Ronald L. Longwell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
PROPERTY LOCATION Located in the Copper Creek area of the Galiuro Mountains, the Old Reliable is on ground first claimed for mineral value during the Civil War. The deposit was mined sporatically from 1880 to 1919 and again in 1953 and 1954, with a total of about 30,000 tons of ore removed. The ore body is a near vertical breccia pipe containing approximately 4,000,000 tons of 0.80% copper with mineralization occuring as chalcocite, chalcopyrite, malachite, chalcanthite, and chrysocolla. The host rocks are extrusive lavas of cretaceous age which were intruded and mineralized by Copper Creek Granodiorite, which is Laramide in age. The ore zone, which occurs on the toe of a ridge, is about 300 feet by 600 feet in plan, with the bulk of the deposit extending from the surface to a depth of 500 feet.